Rethinking Public Auditing Institutions: Empirical Evidence from Swiss Municipalities - Mark Schelker; Reiner Eichenberger (Center for Research in Economics, Management and the Arts (CREMA), 2008)
In the economic literature various political institutions designed to control the government have been analyzed. However, an important institution has been neglected so far: independent auditing institutions with an extended mandate to analyze the budget draft and individual policy proposals. We argue that auditors with an extended mandate improve transparency and provide essential information on the impact of policy proposals on common pool resources. This leads to less wasteful spending and a more efficient allocation of public resources. We empirically analyze the policy impact of local auditors with an extended audit mandate in Switzerland. Auditors, who can evaluate and criticize policy proposals ex ante to policy decisions, significantly reduce the general tax burden and public expenditures. We find similar results with different datasets. These results are robust to various changes in the econometric specification.
Keywords: D70; H10; 330; auditor; audit court; special interests; political economics; public finance